Fatores psicossociais envolvidos na prática do ensino híbrido implantado por profissionais da educação básica - Ribeiro, Victor Abreu (My University, 2025)
It can be said that Hybrid Education (EH) is the articulation of teaching and learning processes that involve the mixing and integration of areas, professionals and students, in different spaces and times, mediated by technology. Recently, basic education schools have resorted to EH as a strategy aimed at meeting the health requirements linked to the pandemic situation caused by SARS-Cov-2. The way in which it was implemented generated a demand that needed to be met with greater urgency: the technical and adequate development of teachers in a short period of time and with maximum health concerns. The EH, often understood as an innovative teaching instrument (because it is capable of reconciling spaces, times and projects, in-person and online), required the teacher to play the role of designer of new pedagogical tools and, for this reason, could not be implemented satisfactorily in such a short time. Based on the perception of this problem, we sought to identify the psychosocial factors present in the practice of EH developed by professionals in basic education Schools in the private education network in the city of Caxias do Sul. To this end, the methodology was quantitative - through the use of the Psychosocial Risk Assessment Protocol at Work (PROART) questionnaire developed by Facas (2013) - applied online to 65 people, combined with the qualitative approach through a semi-structured interview with 10 teachers who worked in basic education institutions and who practiced EH in the six months before the research. The results indicate the coexistence of protective and risk factors in work contexts. The first ones are more linked to the individual attitudes and behaviors of workers and the presence of a more collective school management. The risk factors, on the other hand, are more linked to the prescribed organization of work within the context of compulsory work and scarce preparation. In response to the demands encountered, the script 'Technology and Teacher Well-being: Working on Managers' Awareness to Develop People' was suggested, as a technical product which seeks to promote work redesign actions and organizational practices that collaborate in strengthening protective factors in the context of EH and the implementation of new technologies in the classroom. [resumo fornecido pelo autor]
Pode-se afirmar que o Ensino Híbrido (EH) é a articulação dos processos de ensino e aprendizagem que implicam a mistura e integração de áreas, profissionais e alunos, em espaços e tempos distintos, mediados pela tecnologia. Recentemente, escolas de Educação Básica têm recorrido ao EH como estratégia voltada às exigências sanitárias ligadas à pandemia provocada pelo SARS-Cov-2. O modo como o EH foi implantado gerou uma demanda a ser atendida com maior urgência: o desenvolvimento técnico e adequado de professores num período curto de tempo e com máxima preocupação sanitária. O EH, frequentemente entendido como um instrumento de ensino inovador (por ser capaz de conciliar espaços, tempos e projetos, presencial e online), exigiu do professor um papel como designer de novas ferramentas pedagógicas e, por esta razão, não poderia ser implantado satisfatoriamente em tão pouco tempo. A partir da percepção deste problema, buscou-se portanto identificar os fatores psicossociais presentes na prática do EH desenvolvida por profissionais da Educação Básica da Rede Privada de Ensino na cidade de Caxias do Sul. Para tal, a metodologia foi quantitativa - através do uso do questionário Protocolo de Avaliação dos Riscos Psicossociais no Trabalho (PROART) desenvolvido por Facas (2013) - aplicado em modalidade online para 65 pessoas, unida à abordagem qualitativa através de uma entrevista semi estruturada com 10 professores que trabalharam em instituições da Educação Básica e que praticaram o EH nos seis meses anteriores à pesquisa. Os resultados indicam a coexistência de fatores de proteção e de risco nos contextos de trabalho. Os primeiros estão mais vinculados às atitudes e comportamentos individuais dos trabalhadores e à presença de uma gestão escolar mais coletiva. Já os fatores de risco estão mais ligados à organização prescrita do trabalho dentro do contexto de compulsoriedade e de escassa preparação. Como resposta às demandas encontradas, sugeriu-se o roteiro 'Tecnologia e Bem-estar do Professor: Sensibilizar Gestores para Desenvolver Pessoas', como produto técnico que busca promover ações de redesenho de trabalho e práticas organizacionais que colaborem no fortalecimento dos fatores de proteção no contexto do Ensino Híbrido e de implantação de novas tecnologias em sala de aula. [resumo fornecido pelo autor]
Keywords: Ensino híbrido; Educação básica; Trabalho - Aspectos psicológicos; Trabalho - Aspectos sociais; Saúde e trabalho; Blended learning; Basic education; Work - Psychological aspects; Work - Social aspects